Peningkatan Status Gizi Anak Melalui Pendekatan Pemberdayaan Keluarga Dalam Memanfaatkan Pangan Lokal - Maria Sambriong; Yoani Maria (Poltekkes Kemenkes Kupang, 2021)
Abstract: Introduction: Family empowerment can be used to improve the nutritional status of children under two years of age by utilizing local food available in the community. Purpose: This study aims to determine the effect of family empowerment in the use of local food on the improvement of the nutritional status of children under two years of age through a